“Degradation of an already marginalized existence” Urban intervention project in the San José Commune, in Manizales, Colombia - Cardona – Arias, Nicolás (Universidad Francisco de Paula Santander, 2023)
The article postulates as an objective to identify the social implications of the execution of the Project of National Social Interest Central West of Colombia, on the inhabitants of the San José Commune who were relocated to the San Sebastián neighborhood of the city of Manizales. In the work it is argued that the urban project, contrary to improvement, affected the quality of life of many people located in this part of the city. The study was oriented under the interpretivist paradigm with a historical-hermeneutic approach and the use of the methodology known as case study. Field visits were carried out where semi-structured interview guides were applied to people relocated to the San Sebastián neighborhood and ethnography was used. Bibliographic material was also reviewed. In the investigation, the theoretical conceptions referring to the right to the city and urban marginalization from different analytical positions were fundamental. It is concluded that the San José Macroproject, in its attempt to find alternatives to the housing problems in the sector, generated new problems, informality and labor instability increased among the population when it was transferred to a peripheral neighborhood of the city and poverty. in many homes increased.